2018
DOI: 10.1088/1361-6560/aadf25
|View full text |Cite
|
Sign up to set email alerts
|

The impact of secondary fragments on the image quality of helium ion imaging

Abstract: Single-event ion imaging enables the direct reconstruction of the relative stopping power (RSP) information required for ion-beam therapy. Helium ions were recently hypothesized to be the optimal species for such technique. The purpose of this work is to investigate the effect of secondary fragments on the image quality of helium CT (HeCT) and to assess the performance of a prototype proton CT (pCT) scanner when operated with helium beams in Monte Carlo simulations and experiment. Experiments were conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 70 publications
4
48
2
Order By: Relevance
“…In recent studies, the RSP accuracy achieved by some of these prototypes has been reported to be better than 1.6% for three inserts (Esposito et al 2018) and 1.39% for seven inserts (Giacometti et al 2017). For the same seven inserts, Volz et al (2018) achieved accuracy better than 1% using helium ions with a 30 pCT prototype. An alternative for obtaining RSP images of high accuracy is dual energy X-ray CT (DECT) (Yang et al 2010), where several studies (Hünemohr et al 2013, Bourque et al 2014, Hudobivnik et al 2016, Möhler et al 2016, Han et al 2016, Taasti et al 2016, Lalonde et al 2017, Saito & Sagara 2017b, Almeida et al 2018 have 35 demonstrated the potential of reaching an RSP accuracy of about 1%.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the RSP accuracy achieved by some of these prototypes has been reported to be better than 1.6% for three inserts (Esposito et al 2018) and 1.39% for seven inserts (Giacometti et al 2017). For the same seven inserts, Volz et al (2018) achieved accuracy better than 1% using helium ions with a 30 pCT prototype. An alternative for obtaining RSP images of high accuracy is dual energy X-ray CT (DECT) (Yang et al 2010), where several studies (Hünemohr et al 2013, Bourque et al 2014, Hudobivnik et al 2016, Möhler et al 2016, Han et al 2016, Taasti et al 2016, Lalonde et al 2017, Saito & Sagara 2017b, Almeida et al 2018 have 35 demonstrated the potential of reaching an RSP accuracy of about 1%.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] X-ray CT images are typically not acquired in treatment position and not prior to every treatment fraction, in order to keep treatment time short and imaging dose low enough that they do not compromise the dose benefit of proton therapy. 10 Direct imaging of RSP using proton computed tomography (pCT) [11][12][13][14][15][16] has been proposed to increase accuracy and to allow for a frequent, dose efficient acquisition in treatment position. Accuracies achievable with current prototypes are comparable to state-of-the art clinical dual energy x-ray CT. 7,[17][18][19] A further reduction of imaging dose can be achieved by modulating the imaging fluence field during the acquisition and thereby achieving a task-specific image quality.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this work was to investigate the effect of such events on the accuracy of pCT with the prototype detector developed by the US pCT collaboration (Bashkirov et al 2016a, Johnson et al 2017 in Monte Carlo simulations. We investigate the performance of the usual 3 σ WEPL filter and assess the potential of using the ∆E-E filtering technique recently proposed to identify nuclear fragmentation events in helium ion CT (HeCT) with the scanner energy/range detector (Volz et al 2018) to identify nuclear interaction events in pCT.…”
Section: Introductionmentioning
confidence: 99%